Lymph Nodes-On-Chip: Promising Immune Platforms for Pharmacological and Toxicological Applications - Shanti, Aya; Hallfors, Nicholas; Petroianu, Georg A; Planelles, Lourdes; Stefanini, Cesare (Frontiers in Pharmacology, 2021)
Organs-on-chip are gaining increasing attention as promising platforms for drug screening and testing applications. However, lymph nodes-on-chip options remain limited although the lymph node is one of the main determinants of the immunotoxicity of newly developed pharmacological drugs. In this review, we describe existing biomimetic lymph nodes-on-chip, their design, and their physiological relevance to pharmacology and shed the light on future directions associated with lymph node-on-chip design and implementation in drug discovery and development.